Indonesia's Downstream Strategy As An Economic Geopolitics - Andri Hermawan; Imas Trimayanti (Jurnal Ekuisci, 2026)
Background. Indonesia entered the 2020s with an ambitious economic geopolitical strategy unprecedented in scale: an industrial downstream processing (downstream) program based on raw material export bans that mandates domestic processing investment. This policy, aggressively pursued since the Joko Widodo administration through the 2020 nickel export ban and extended to bauxite, copper, and other commodities, represents a paradigm shift from Indonesia as a raw material exporter to an exporter of high-value-added products. Aims. This study comprehensively analyzes the downstream processing program's impact on: (1) global supply chain reconfiguration—particularly electric vehicle battery, steel, and aluminum supply chains; (2) Indonesia's economic growth and national industrial restructuring; (3) geopolitical dynamics and responses from trading partner nations; and (4) quantitative projections and economic growth scenarios for Indonesia over the next 10–20 years if the downstream processing program is sustained consistently. Methods. Using a mixed-methods approach integrating macroeconomic data analysis, Global Value Chain (GVC) simulation, and prospective scenario modeling, this study finds that consistent downstream processing has the potential to propel Indonesia's GDP from USD 1.33 trillion (2024) toward USD 3.2–4.8 trillion by 2035 and USD 5.5–8.2 trillion by 2045—positioning Indonesia among the world's 4th to 6th largest economies. Conclusion. However, realizing this potential requires coherent policy execution, massive infrastructure investment, strengthened human resource capabilities, and astute management of geopolitical risk.